Morbidity and mortality in HIV-exposed uninfected children. (September 2015) - Thorne, Claire; Idele, Priscilla; Chamla, Dick; Romano, Sostena; Luo, Chewe; Newell, Marie-Louise
Approximately 1.5 million HIV-positive women become pregnant annually. Antiretroviral therapy (ART) is central to prevention of mother-to-child transmission and maternal ART continued postpartum allows breastfeeding for at least 1 year of life, with important benefits for the child. In the pre-ART era, it was suggested that HIV-exposed uninfected (HEU) children may be at higher morbidity and mortality risk than children of HIV-negative mothers, associated with maternal illness and death and the lack, or limited duration, of breastfeeding as recommended for preventing mother-to-child transmission at that time. This review summarizes the evidence on morbidity and mortality risk in HEU children compared with HIV-unexposed children, and assesses the likely impact of roll-out of ART, which prolongs maternal survival and allows breastfeeding.